RF-sensor for a local position measurement system - Stelzer, Andreas; Fischer, Alexander; Weinberger, F.; Vossiek, Martin (8th NDE Symposium: Nondestructive Detection and Measurement for Homeland Security Conference, 2003)
In this paper a novel local position measurement (LPM) technology is presented. The LPM system operates in the 5GHz ISM band and consists of lightweight transponders of which the 3-D position is measured, and base stations located around the measurement field. Transponder and base stations operate similar to conventional radar systems and consist of RF electronics as well as signal processing elements. The RF-part in the transponders is the key element for the position measurement system. The measurement accuracy of the LPM system is in the range of some centimeters despite a high measurement rate of 1000 measurements per second.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.rfsens
Keywords: 3-D positioning; Distance measurement; Local position measurement; RF-front-end